Pengaruh Detailing Tulangan Portal Pengekang pada Pemodelan Numerik Dinding Bata Terkekang Akibat Pembebanan Monotonik - Aryadenata, Dimas; Suarjana, Made; Kusumastuti, Dyah; Lim, Erwin (Jurnal Teknik Sipil, 2026)
Confined masonry walls are commonly found in low-rise buildings in Indonesia, which are typically constructed without structural analysis. Even in structural analysis, the contribution of masonry walls to the strength and stiffness of the structure is often disregarded. This study focuses on the numerical modelling development of confined masonry walls due to the influence of the absence of frame reinforcement detailing under monotonic loading using an equivalent diagonal strut model. The modeling was carried out by comparing specimens with and without reinforcement detailing of the confining frame, which is commonly found in Indonesia. The results show that the numerical model can effectively simulate the response of confined masonry walls. However, a significant error difference between the two tested specimens indicates the limitations of the model in capturing the beam-column joint failure phenomenon before the masonry wall failure in specimens without confining frame detailing.